Pengaruh Kelengkapan Produk terhadap Loyalitas Pelanggan Gudang Masker (GM Store) Banda Aceh - Firda, Zulpiana; Razak, A.; Suraiya, Nana; Mursalin, Mirja (Jurnal Ragam Pengabdian, 2025)
Customer loyalty is a strategic factor in retail business sustainability, particularly in the cosmetics and skincare industry which has a high level of competition. One of the determinants that can potentially increase customer loyalty is product completeness. This study aims to analyze the effect of product completeness on customer loyalty at Gudang Masker (GM Store) Banda Aceh. This study uses a quantitative approach with a survey method. The research sample consisted of 97 customers selected using purposive sampling technique. Data were collected through a structured questionnaire with a Likert scale and analyzed using simple linear regression analysis with the help of SPSS version 27 software. The results showed that product completeness had a positive and significant effect on customer loyalty, as indicated by a positive regression coefficient value and a significance level below 0.05. These findings indicate that the more complete the product variations and availability offered, the higher the tendency for customers to make repeat purchases and remain loyal to GM Store. This study provides managerial implications for retail business actors in designing product management strategies to increase customer loyalty, as well as contributing to strengthening the empirical literature on consumer behavior in the cosmetic retail sector in the local market context.